Pemanfaatan SIPD sebagai Sistem Informasi Akuntansi Manajemen dalam Perencanaan Anggaran Kecamatan Sidoarjo - Firdaus, Dewi Anisa; Anwar, Chairil (Jurnal Mahasiswa Manajemen dan Akuntansi, 2026)
This study aims to examine the use of the Regional Government Information System (SIPD) as a management accounting information system in the budget planning process at the Sidoarjo District Office. This research applies a qualitative descriptive approach, with data obtained through semi structured interviews, observation of SIPD based budget planning activities, and documentation of planning and budgeting records. The findings show that SIPD has been used effectively to support budget planning, especially in preparing activity budgets, setting budget ceilings, and determining program priorities. The system enhances data integration, consistency, and transparency in the planning process. However, several challenges still exist, including limited staff competence and technical constraints of the system. These results show that although SIPD has an important role in improving the quality of budget planning, its effectiveness depends on user capability and system optimization. Therefore, strengthening human resource capacity and improving system performance are essential to achieving more effective and accountable budget planning.